Public Wealth in the United States - Gonguet, Fabien (IMF Working Papers; Working Paper ;, 2019)
We analyze the US public sector balance sheet and project it forward under the assumption that current policies remain in place. We first document the history of the balance sheet and its components since World War II, with a detailed account of its evolution during and after the global financial crisis. While, based on assets and liabilities alone, public sector net worth is negative, additional challenges arise from commitments to future spending implied by current legislation and demographic trends. To quantify the risks to the balance sheet, we then apply the macroeconomic scenarios from the Federal Reserve's bank stress test to the public sector balance sheet.